Managing information across the enterprise - Wysocki, Robert K.; DeMichiell, Robert L. (New York : John Wiley and Sons, 1997)
This book is about: Enabling the enterprise; Redesigning business processes; Enabling business functions;...
Keywords: Management; Information technology; Management information systems; Information technology -- Management